Assessment of chemotherapy strategy using bevacizumab for non-squamous non-small cell lung cancer in a real-world setting: A multi-institutional observational study. (2016) - Higashiguchi, Masayoshi; Kijima, Takashi; Morimura, Osamu; Osa, Akio; Suzuki, Hidekazu; Inoue, Takako; Kagawa, Hiroyuki; Ueno, Kiyonobu; Hirashima, Tomonori; Kumagai, Toru; Imamura, Fumio; Mori, Masahide; et al.
Abstract: Micro-abstract: We retrospectively analyzed 162 patients with non-squamous non-small cell lung cancer (NSCLC) who underwent first-line chemotherapy with bevacizumab (BEV); 127 patients without driver oncogenes, 17 patients with EGFR major mutations, 12 patients with ALK rearrangements, 4 patients with EGFR minor mutations and 2 patients with rare types of histology. Background: BEV has been approved for treatment of non-squamous NSCLC and is authenticated as one of the key drugs in the treatment of advanced non-squamous NSCLC. Patients and methods: We retrospectively analyzed patients with stage IIIB/IV non-squamous NSCLC who underwent chemotherapy with BEV in first-line setting. Results: In 162 patients who underwent chemotherapy combined with BEV as first-line treatment, the median overall survival (OS) and progression-free survival (PFS) were 23.5 months and 6.8 months, respectively. The PFS did not differ significantly by the presence of driver oncogenes. In patients without driver oncogenes, more patients who received carboplatin plus pemetrexed with BEV could complete at least 4 cycles of induction therapy and more of these patients proceeded to maintenance therapy than those who received carboplatin plus paclitaxel with BEV, which resulted in better outcome associated with carboplatin plus pemetrexed with BEV. Continuation of BEV beyond first progression did not show any survival benefit. In EGFR mutation-positive patients, the order of BEV-containing regimen and TKI did not influence on OS. None of 18 patients with brain metastases detected at diagnosis developed intracranial hemorrhage. Conclusions: PFS of first-line chemotherapy using BEV was not influenced by the existence of driver oncogenes. In patients without driver mutations in real clinical practice, as the first-line partner regimen with BEV, carboplatin plus pemetrexed may be more feasible as compared to carboplatin plus paclitaxel. BEV use beyond first progression did not deliver significant survival benefit. BEV was safe for brain metastases.